2015
DOI: 10.3126/ojn.v5i2.15220
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Ceramic Brackets with Different Base Designs: An in-vitro Study

Abstract: Ceramic brackets were introduced in 1987 as a more esthetically pleasing alternative to stainless steel brackets. 1 Two types of ceramic brackets are available according to their distinct differences during fabrication, they are: polycrystalline and monocrystalline (single-crystal) aluminas. 2,3 Both polycrystalline and monocrystalline ceramic brackets possess various base designs such as grooves, beads, or round pits for the purpose of mechanical interlocking between the brackets and the teeth. 4 As bracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The result of the present research are in agreement with Olsen, Chaudhary, and Bakhadher who found that entire bonding material remained on tooth surface. [11][12][13] Multiple factors can influence bond strength scores, namely, geometric form of bracket base, nature of composite used, condition of the enamel surface, 14 and adhesive forces. 15,16 Further research is recommended to determine the debonding character of clarity brackets when removed with instruments designed especially for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the present research are in agreement with Olsen, Chaudhary, and Bakhadher who found that entire bonding material remained on tooth surface. [11][12][13] Multiple factors can influence bond strength scores, namely, geometric form of bracket base, nature of composite used, condition of the enamel surface, 14 and adhesive forces. 15,16 Further research is recommended to determine the debonding character of clarity brackets when removed with instruments designed especially for this purpose.…”
Section: Discussionmentioning
confidence: 99%